Rousseau’s Politics of Taste - Holley, Jared (Edinburgh University Press, 2025)
Rousseau’s Politics of Taste challenges the popular but partial pictures we have of Rousseau as an inconsistent ‘ancient’ utopian or a ‘modern’ abstract philosopher with a systematising spirit. Combining intellectual history and political theory, it reinterprets his understandings of pleasure and happiness, judgment and amour-propre, inequality, the general will and, above all, taste. Rousseau’s readers have long recognised the complex tensions in his thought. By reconstructing his theory of taste as a kind of modern Epicureanism, this book provides a way of articulating neglected patterns in those tensions and, a new understanding of what he was attempting to achieve with his political thought.